Crisis in whiteness: white workingmen's narratives and the American dream - Morrison, Joseph J., author; Ishiwata, Eric, advisor; Cespedes, Karina, committee member; Souza, Caridad, committee member; Brinks, Ellen, committee member (Colorado State University. Libraries, 2013)
This project examines the ways in which white working class men make sense of their own socioeconomic positioning in the contemporary U.S. economy. This is accomplished through the exploring of white workingmen's narratives of the American Dream, and how these narratives are informed by the race, class and gendered identities of the white working class men expressing them. Specifically, this project is a case study of five self-identified white working class men living in Upstate New York's Chemung, Onondaga, Tioga, and Tompkins Counties. Through this project's findings the researcher hopes to chart a new course for the field of Whiteness Studies into the twenty-first century.